Alkaline Phosphatase is an Independent Risk Factor for Periprosthetic Fractures in Total Joint Arthroplasty. (10th February 2023) - Lung, Brandon E.; Kim, Matthew; McLellan, Maddison; Callan, Kylie; Wang, Edward D.; McMaster, William; Yang, Steven; So, David H.
Abstract : Background: Serum alkaline phosphatase (ALP) is a biomarker for chronic low-grade inflammation along with hepatobiliary and bone disorders. High abnormal ALP levels in blood have been associated with metabolic bone disease and high bone turnover. Methods: All primary total hip and knee arthroplasties from 2005 to 2019 were queried from the National Surgical Quality Improvement Program database. Patients with available serum ALP levels were included and stratified to low (<44 IU/L), normal (44 to 147 IU/L), and high (>147 IU/L). A risk-adjusted multivariate logistic regression was used to analyze ALP as an independent risk factor of complications. Results: The analysis included 324, 592 patients, consisting of 11, 427 low ALP, 305, 977 normal ALP, and 7, 188 high preoperative ALP level patients undergoing total joint arthroplasty. Adjusted multivariate logistic regression analysis showed high ALP level patients had an overall increased risk of readmission within 30 days of surgery compared with the control group (odds ratio [OR], 1.69; P < 0.01). High ALP patients also had an increased risk of postoperative periprosthetic fracture (OR, 1.6), postoperative wound infection (OR, 1.81), pneumonia (OR, 2.24), renal insufficiency (OR, 2.39), cerebrovascular disease (OR, 2.2), postoperative bleeding requiring transfusion (OR, 1.83), sepsis (OR, 2.35), length of stay > 2 days (OR, 1.47), Clostridium difficile infection (OR, 2.07), and discharge to a rehab facility (OR, 1.41) (all P < 0.05). A low ALP level was also associated with increased postoperative bleeding transfusion risk (OR, 1.12; P < 0.01) and developing a deep vein thrombosis (OR, 1.25; P = 0.03). Conclusion: Abnormal serum ALP levels in patients undergoing primary total joint arthroplasty are associated with increased postoperative periprosthetic fracture risk and medical complications requiring increased length of stay and discharge to a rehabilitation facility.